Science Education Data Analysis to Improve Student Achievement: An In-Depth Bibliometric Analysis - Habibi, Ahmadi Martha; Al Mubarok, Fahmi Ulum; Chusniatun, Chusniatun; Shobahiya, Mahasri; Musyaffa, Zaim Hilmi (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
This study was conducted to map and analyze the development of research on Science Education Data in publications that have been indexed in Scopus. The method applied is bibliometric analysis, which explores information from publications related to "Data of Science Education" from 2015 to 2024 in the Scopus database. The analysis process involved the use of tools such as Excel and R/R-Studio. The analysis results were visualized using VOS viewer to display keyword occurrences and document citations simultaneously. Within this study's framework, 1092 publications that met the set criteria were identified. The findings of this study indicate an annual growth of 21.32%, peaking in 2021. The United States was identified as the primary contributor in the number of publications, with the University of Nigeria as the most productive affiliate. The author who achieved the highest productivity in the Data of Science Education theme was Ali, N. By detailing these statistics and trends, this study provides a comprehensive overview of the literature in the education domain, while conveying recommendations for research directions that could be undertaken in the future. It is hoped that the results of this study make a valuable contribution to the in-depth understanding of data in the context of Science Education.